Efficacy and safety of the trans-obturator tape for female stress urinary incontinence - Roy, Priyankur; Biswas, Bivas; Hokabaj, Shaheen; Garg, Ruchika; S., Sujatha M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To assess the safety and efficacy of Trans-obturator tape (TVT-O) for female stress urinary incontinence (SUI). Methods: A cohort of 35 cases of SUI and underwent TVT-O procedure over a period of 4 years. Pre-operative evaluation included pelvic examination, one hour pad test, urodynamic study, urinary diary and baseline haematological tests. Post-operatively all women had post-void residual volume and were followed up for 3 years. Results: The mean age of the patients was 47±9.5 years. TVT-O alone was done in 58.1% of cases. 41.9% of cases had TVT-O done as a concomitant procedure. The median duration of follow-up was 48 months. The overall objective and subjective cure rate was 92.3% with failure rate of 7.7%, 12.9% of women reported post-operative thigh pain and 6.5% patients had immediate post-operative urinary retention. 16.1% of the patients had post-operative voiding dysfunction. No major complications were encountered in these patients. Conclusions: TVT-O is a safe, easy and effective minimally invasive procedure for female SUI with minimal acceptable complications.